Obliczysz :
(x⁸ : x⁶)³ + 3 · (x² · x⁴)
_________________________
x² · 4 (x⁶ : x⁵)
_________________________ =
( x ²)³ + 3* x⁶
= ----------------------- =
x²*4 * x
x⁶ + 3x⁶
= --------------- =
4x³
4x⁶
= ------------ = x⁶⁻³ = x³
x^8:x^18 +3x^2 * x^4=x^-10+3x^2=2x^-8
=1/4 ^-5
x^2*4x^6:4x^5=4x^3
(x⁸:x⁶)³+3·(x²·x⁴) : x² · 4 · (x⁶:x⁵) = (x²)³+3·x⁶ : x²·4·x=x⁶+3x⁶ : x²·4·x=x⁶+3x⁶ : x²·4·x = 4x⁶ : x²·4·x = 4x⁶ : 4x³=x³
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
(x⁸ : x⁶)³ + 3 · (x² · x⁴)
_________________________ =
x² · 4 (x⁶ : x⁵)
( x ²)³ + 3* x⁶
= ----------------------- =
x²*4 * x
x⁶ + 3x⁶
= --------------- =
4x³
4x⁶
= ------------ = x⁶⁻³ = x³
4x³
x^8:x^18 +3x^2 * x^4=x^-10+3x^2=2x^-8
=1/4 ^-5
x^2*4x^6:4x^5=4x^3
(x⁸:x⁶)³+3·(x²·x⁴) : x² · 4 · (x⁶:x⁵) = (x²)³+3·x⁶ : x²·4·x=x⁶+3x⁶ : x²·4·x=x⁶+3x⁶ : x²·4·x = 4x⁶ : x²·4·x = 4x⁶ : 4x³=x³